Estimation of Laterite Nickel Resources Using Ordinary Krigging Method at PT Vale Indonesia Nuha District East Luwu South Sulawesi Province - Rauf Husain, Jamal; Bakri, Hasbi; Adnan Firdaus (CV Insight Publisher, 2023)
Resources have an economic value, form, quality, quantity rate, geological characteristics, and endurance to be economically extracted. Mineral resources are grouped according to their degree of geological certainty into the categories of assumed, indicated, and measured. The research aims to assess the potential resource potential of nickel laterite and the spread of the rate of mineralization of nickel in the research area using the geostatistical method of Ordinary Kriging. The research methodology is based on conducting statistical and geostatic analysis, starting with univariate statistical analysis, spatial statistics, bivariate statistics, and resource estimates. The results of the statistical calculation using the Ordinary Kriging for limonite and saprolite zones with an average gap of 25 meters and an average depth of 20 meters with their parallel directions to the west, north-northeast, south-east, southeast, and west-southwest obtained a total volume of 119,920,468 m3 with a tonnage of 201,798,081 tons and a mean rate of nickel laterite of 1.56% Ni. Based on the results of an evaluation, it can be concluded that the number of nickel laterite deposits with a cut-off grade of 1.4% is 89,804,733 tons and the average rate is 1.83% Ni.